Thawing Arctic Realities: Analyzing Arctic Security through the Lens of Arctic Exceptionalism and Great Power Politics - Ragna Mathisen Heggelund 1998- (2023)
This thesis explores the intricate and evolving landscape of Arctic security dynamics, offering a comprehensive examination that combines the perspectives of Arctic exceptionalism and great power politics. In the face of climate change, the Arctic region has gained increased attention due to its unique vulnerabilities, environmental transformations, and great power politics. This study employs a theoretical framework that incorporates Arctic exceptionalism's focus on the Arctic's exceptional vulnerabilities and constructivism's emphasis on shared knowledge, norms, and identities. The research reveals a nuanced and multi-dimensional understanding of Arctic security emerges when analyzing Arctic exceptionalism's unique perspective alongside constructivism's insights. The Arctic exceptionalist lens highlights the Arctic's distinctive responses to global climate shifts, emphasizing the intricate connection between environmental security, cultural heritage, and geopolitical competition within the Arctic region. Furthermore, the study investigates the implications of climate change on the Arctic ecosystem, Arctic peoples, the region's vast resource potential, and the ensuing opportunities and challenges. It examines the potential for geopolitical competition in the Arctic, emphasizing that the melting Arctic's strategic significance extends beyond environmental concerns. Additionally, this thesis discusses the influence of global events on Arctic security. It explores the implications of Russia's actions in Ukraine on Arctic cooperation and analyzes the role of great powers in shaping the Arctic's security landscape. The research highlights the interconnectedness of Arctic security with broader global dynamics, emphasizing that the Arctic's distinctiveness does not preclude its susceptibility to external influences. This thesis underscores the importance of adopting a holistic approach to Arctic security analysis, bridging the gap between Arctic exceptionalism and global interconnectedness. It provides valuable ...